Video Art: Accelerationism and the Reification of Desire - Kirlew, Akil (Auckland University of Technology, 2014)
This research project explores the creative links between the production and circulation of video-based artworks and the dominance of capitalist-based forms of subjectivity. More specifically, I seek to determine whether digital video can be used in a manner that avoids complicity in the reification of desire. My use the word “desire” is borrowed from Gilles Deleuze for whom desire is a productive force that exists within and between various entities. By “reification of desire” I mean the method by which the cultural industries isolate and decontextualize elements of human social relations in an attempt to develop products that ostensibly satisfy the yearnings of the public. My research attempts to determine if this reification and commodification of desire can be resisted via aesthetic tactics such as allegory, masochism, and parody. I argue that these tactics may be viewed as components of an overarching strategy of accelerationism (Noys, Shaviro). In Chapter 1 (Video Economics), I explore video art’s position within the broader framework of the cultural industries. In Chapter 2 (Body Doubles), I formulate my methodological approach via an examination of masochism, allegory, and accelerationism. In my third and final chapter (Andrea Fraser’s Untitled), I bring the subjects of the first two chapters into relation via a discussion of Andrea Fraser’s artwork Untitled. While this is a written thesis, I also have an artistic practice that makes use of performance, creative writing, and video. Consequently, I briefly discuss my own creative work (in chapter 2) as a means of clarifying my intentions.
Keywords: Accelerationism; Reification; Masochism; Desire